Faktor Yang Mempengaruhi Purchase Intention Smartphone Dengan Brand Image Sebagai Mediasi Di Kota Batam - Julianto, Tri; Kesumahati, Erilia (Jurnal Manajerial, 2024)
Background – Nowadays there are many smartphone brands that make consumers confused when they have to choose what smartphone is good to buy and use everyday, therefore this research was conducted to prove what are the main factors for consumers when they want to buy a smartphone. Aim – The purpose of this research was to find out the factors that influence consumer purchase intentions when they want to make a purchase of a smartphone brand in Batam City. Design / Methodology / Approach – The research method used is the survey techniques by distributing questionnaires as a means of extracting data. The distribution of the questionnaires produced results in the form of 360 respondents from the people of Batam City who wanted or intended to purchase Smartphones in the future. This study uses validity and reliability tests to test the feasibility of the questionnaire and the results of the respondents. In addition, this study also uses path coefficient as a method of data analysis with the aim of seeing the direct and indirect relationships of each variable. Findings – Based on the results that have been analyzed, it proves that there are several factors that influence consumer Purchase Intention, such as Brand Trust and Service Quality, but there are also factors that do not affect consumers, such as Brand Image. Conclusion – This shows that Smartphone business must convince consumers so that they have a strong sense of trust in the product and services provided must be as good as possible with the aim that consumers will feel comfortable when they are in the store. Research Implication – The conduct of this research will have an impact, especially on smartphone companies where the company will know what factors consumers are looking for when visiting a store. Limitations – The limitation of this research only involves the area around the author in Batam City.